Development of Fuzzy Logic Controller for Magnetic Levitation system / Haslina Adnan - Adnan, Haslina (2008)
Magnetic Levitation (Maglev) system is nonlinear and complex system. The purpose of this project was to develop Fuzzy Logic Controller (FLC) to the Maglev system. Fuzzy Logic Controller resemble human decision making. This controller is used to control the tracking performance of the Maglev system. Fuzzy Logic Controller is designed by using MATLAB Fuzzy Toolbox and the Magnetic Levitation control system block diagram environment is designing using SIMULINK. There is several method uses to control the Maglev system such as PID controller. The result was produced after testing was completed and show in the experimental results. The comparison between the both PID and Fuzzy controller performance will be presented in this thesis